Determination of the solubility and thermodynamic properties of albendazole in a binary solvent of ethanol and water. (2nd January 2021) - Yang, Wen-Zhu; Fan, Guo-Qing; Zhang, Ting-Ting; Li, Dong-Bo; Pei, Lin-Lin; Huang, Ruo-Yue; Yin, Dai-Ping; Zhang, Li; Peng, Guang-Neng; Shu, Gang; Yuan, Zhi-Xiang; Lin, Ju-Chun; et al.
ABSTRACT: The solubility of albendazole (ABZ) in a binary system of ethanol and water were determined experimentally by using a static analytical method within the temperature range (288.95 to 317.25) K under atmospheric pressure (p = 0.1 MPa). It was observed that the solubility of ABZ is not only depended on temperature but also related to the mole fraction of ethanol. Additionally, the obtained solubility data were correlated by employing the CNIBS/R-K model, the modified Apelblat equation and the Jouyban–Acree model. The modified Apelblat equation was proven to give good representation of the experimental solubility data. On the base of the measured solubility, the thermodynamic properties of the dissolution process were calculated. Dissolution of ABZ in these mixed solvents is endothermic, non-spontaneous and enthalpy-driving. This study provides useful information for the design and development of dosage forms of ABZ.